Increases in intracellular calcium perturb blood–brain barrier via protein kinase C-alpha and apoptosis - Rakkar, Kamini; Bayraktutan, Ulvi (Elsevier, 2016)
An increase in intracellular calcium represents one of the early events during an ischaemic stroke. It triggers many downstream processes which promote the formation of brain oedema, the leading cause of death after an ischaemic stroke. As impairment of blood–brain barrier (BBB) accounts for much of oedema formation, the current study explored the impact of intracellular calcium on barrier integrity in relation to protein kinase C, caspase-3/7, plasminogen activators and the pro-oxidant enzyme NADPH oxidase. Human brain microvascular endothelial cells alone or in co-culture with human astrocytes were subjected to 4 h of oxygen–glucose deprivation alone or followed by 20 h of reperfusion (OGD ± R) in the absence or presence of inhibitors for urokinase plasminogen activator (amiloride), NADPH oxidase (apocynin), intracellular calcium (BAPTA-AM) and protein kinase C-α (RO-32-0432). Endothelial cells with protein kinase C-α knockdown, achieved by siRNA, were also exposed to the above conditions. BBB permeability was measured by transendothelial electrical resistance and Evan's blue-albumin and sodium fluorescein flux. Intracellular calcium and total superoxide anion levels, caspase-3/7, NADPH oxidase, plasminogen activator and protein kinase C activities, stress fibre formation, the rate of apoptosis and BBB permeability were increased by OGD ± R. Treatment with the specific inhibitors or knockdown of protein kinase C-α attenuated them. This study reveals successive increases in intracellular calcium levels and protein kinase C-α activity are key mechanisms in OGD ± R-mediated impairment of BBB. Furthermore inhibition of protein kinase C-α may be therapeutic in restoring BBB function by reducing the rate of cytoskeletal reorganisation, oxidative stress and apoptosis.